Capital Structure Decisions and Financial Viability of Firms Quoted on the Premium Board Segment of the Nigeria Stock Exchange - Peters, Ihejirika; Michael, Ndugbu; Gladys, Mbagwu Ijeoma; Josephine, Ojiegbe (Journal of Asian Business Strategy, 2020)
We investigate how corporate capital structure decisions affect financial viability of listed companies on the Premium Board segment of the Nigerian stock market 2010 – 2018. The objectives were to ascertain (1) the extent the proportion of debt in relation to equity influence return on assets, (2) determine the effect of non-current liabilities to net worth ratio on return on assets and (3) to examine the relationship between total liabilities to total assets and return on assets. “Panel data analysis” was used to analyze the data. The “Fixed effects model” as well as the “Random effects model” were estimated. The “Haussmann test” suggested the Fixed effects model for interpretation of results. The empirical analysis revealed mixed relationships between capital structure decisions and financial viability of firms. It is recommended that quoted Companies on the Premium Board should target achieving optimal combination of debt and equity to enhance returns on capital employed as well as sustain their Long-term debt profile to continue to improve the level of return on assets. Finally, listed companies on Premium Board should re-examine their working capital policy to minimize the negative effect of short-term debt on return on total assets; given that long-term liability to total assets ratio exhibit a positive and significant association with return on assets while total liability (current plus non-current) to total assets ratio suggests a negative and significant effect on return on assets.